(untitled) (Research, Society and Development, 2022)
Drugs are the most used resource in health care, however, the risks of their use must be taken into account. Pharmacovigilance is the science responsible for the study of drug-related problems, including Adverse Drug Reactions (ADR). The Trigger Tool methodology investigates ADRs through triggers and has become a complementary measure to the voluntary reporting system, in order to more authentically determine the number of adverse events. This study aimed to apply the Trigger Tool methodology to detect ADRs in intensive care unit (ICU) patients. This is a retrospective, descriptive and cross-sectional study carried out in a high complexity hospital. A list of triggers was created based on the Institute for Healthcare Improvement and an analysis of medical records was performed to investigate suspected ADRs. ADRs were classified as to causality and severity and the triggers had their yields evaluated. During the study period, 100% of ADRs were identified through active search. Through the tracking drugs, 85 ADRs were found. As for causality, most of the reactions were classified as probable, followed by possible, doubtful and definite. Regarding the severity of the reactions, the moderate ones were the most frequent, followed by the severe reactions. “Naloxone”, “vitamin k”, “protamine”, “fexofenadine” and “hydroxyzine” were the highest yielding triggers. The active search for ADRs through the Trigger Toll methodology applied by pharmacists proved to be useful in monitoring events in ICU patients.